Answer :

First of all we have to consider,

and


By simplifying above equations, we get:


3 (2x + y + 2) = 5 (3x – y + 1)


6x + 3y + 6 = 15x – 5y + 5


9x – 8y = 1 …(i)


And, 6 (3x – y + 1) = 3 (3x + 2y + 1)


18x – 6y + 6 = 9x + 6y + 3


3x – 4y = – 1 …(ii)


Now, multiplying (ii) by 2 and then subtracting it from (i) we get:


9x – 6x = 1 + 2


x = 1


Putting the value of x in (ii), we get


3 × 1 – 4y = – 1



Hence, option A is correct

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USMathematics - Board Papers

A father&rsMathematics - Board Papers

Find the value ofRS Aggarwal - Mathematics

Find the value ofRS Aggarwal - Mathematics

A man purchased 4RS Aggarwal - Mathematics